Antarctica and Africa: Narrating alternate futures. (September 2019) - Lavery, Charne
Abstract: Africa has been marginalised in the history of Antarctica, a politics of exclusion (with the exception of Apartheid South Africa) reflected unsurprisingly by a dearth of imaginative, cultural and literary engagement. But, in addition to paleontological and geophysical links, Antarctica has increasing interrelationship with Africa's climactic future. Africa is widely predicted to be the continent worst affected by climate change, and Antarctica and its surrounding Southern Ocean are uniquely implicated as crucial mediators for changing global climate and currents, rainfall patterns, and sea level rise. This paper proposes that there are in fact several ways of imagining the far South from Africa in literary and cultural terms. One is to read against the grain for southern-directed perspectives in existing African literature and the arts, from southern coastlines looking south; another is to reexamine both familiar and new, speculative narratives of African weather – drought, flood and change – for their Antarctic entanglements. In the context of ongoing work on postcolonial Antarctica and calls to decolonise Antarctic studies – such readings can begin to bridge the Antarctica–Africa divide.